Effect of uncertainty in CPT end resistance on predicted monopile head load-displacement responses for offshore wind turbines - ICASP14; Reale, Cormac; Tott-Buswell, Jacques; Prendergast, Luke (My University, 2023)
The increasing demand for renewable energy has led to the rapid growth of the offshore wind sector, leading to larger Offshore Wind Turbines (OWT) being developed in deeper water locations further offshore. The geotechnical design procedures therefore become increasingly uncertain as ground investigations become more challenging, and the use of traditional design methodologies are applied to configurations outside of the datasets from which they were originally derived. This paper evaluates the influence of certain elements of geotechnical uncertainty on the monotonic load-displacement behaviour of laterally loaded monopiles. A traditional Beam on Nonlinear Winkler Foundation (BNWF) model is used to characterise the lateral pile-soil interaction, and the p-y springs are informed using Cone Penetration Test (CPT)-based functions. Geotechnical uncertainty is evaluated through the spatial variability of the CPT end resistance profile. Results suggest that spatial variability in end resistance profiles has limited effect on the pile head displacement predictions, highlighting a potential issue whereby local variations in soil properties may not be captured in p-y only models. This implies other spring-type components associated with diameter-dependency are necessary in the BNWF model to capture rigid pile behavior.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED